Fabrication And Simulation Of Vertical Cavity Surface-Emitting Laser Packaging For Face Recognition In Automotive Applications - Arshad, Khairul Mohd (2024)
This research aims to create a vertical cavity surface emitter laser (vcsel) package with a sophisticated mixer for face recognition in automotive applications, following the international automotive task force (iatf) 16949 industry standard. The vcsel package is created and manufactured using the six sigma method to ensure consistent usability and manufacturing capability, surpassing a capability index of 1.33. Tests have been conducted to verify the conformity of the optical, electrical, and far-field properties of the vcsel. Cracking difficulties emerged on the mixer during heat cycling testing. Ansys models indicate that failure happens at 260°c because of a high pressure of 39 mpa. Various design changes are suggested to address this issue, such as implementing a convex microstructure for the mixer, adjusting its placement on the vcsel chip, and including a light-focusing lens. The simulations have shown that the new design can function within an operational temperature range of up to 260°c. The vcsel packaging method shown is very effective for advanced biometric applications such as demanding smart car face recognition.